Answer:
Option D. 1
Explanation:
Thinking process:
Let the quadratic equation be given by the formula:
![cos^(2) x+ 2 cosx - 2 = 0](https://img.qammunity.org/2019/formulas/mathematics/high-school/zn9a2dfv0tk266y4hpgmrhrawdum4d02a1.png)
then solving the equation using the factorization method:
using the trigonometry identity of cos 2x
then
![Cos2x = 2cos^(2)x - 1](https://img.qammunity.org/2019/formulas/mathematics/high-school/gdvjwqfp7ik71uiryli804n5960epef4zy.png)
Substituting 2Cos²x - 1 gives:
2
![cos^(2) x-1+cos^(2)x-2= 0](https://img.qammunity.org/2019/formulas/mathematics/high-school/vd7fimaqcdhbelfy4r5w3mmafldyu5018m.png)
rearranging gives:
![3cos^(2)x = 3\\ cosx = √(1) \\ = 1](https://img.qammunity.org/2019/formulas/mathematics/high-school/a5cnu1hiup9i7s6g1adxh9t375u7u8km7c.png)
hence cosx = 1